Satisfaccion de la calidad del cuidado de enfermeria pre-intraoperatorio en pacientes intervenidos a cirugia de mama , Instituto Nacional de Enfermedades Neoplasicas - Palomino-Sahuiña, Milagros-Luciana (2022)
The essence of nursing is patient care, having as a fundamental axis in the processes of quality care; however, sometimes due to the workload, reduced time in care, lack of protocols, training, staff attitudes, among other aspects; affect the quality of nursing care, which generates dissatisfaction in patient health care. Objective: To determine the level of satisfaction with the quality of preoperative and intraoperative nursing care in patients undergoing breast surgery at the National Institute of Neoplastic Diseases, 2020. Method: Quantitative, descriptive, cross-sectional, prospective. The population consisted of 664 patients undergoing breast surgery, the sample size was 191 patients by probabilistic, simple random sampling, the instrument used to collect the data was a questionnaire, validity was carried out through trial of 8 experts whose value was 0.030 and for reliability the Kuder Richardson test was applied whose value is 0.81 obtaining high reliability. Results: The level of satisfaction of the quality of preoperative and intraoperative nursing care 59.16% of the patients undergoing breast surgery considered to be moderately satisfied with the nursing care received. Conclusions: Satisfaction with the quality of nursing care in the preoperative and intraoperative area is moderately satisfied and dissatisfied, so it is necessary to reinforce care actions that improve the perception of patients in the area.